Wood Properties of Three Fruit Tree Species Planted in Central Kalimantan, Indonesia - Haruna Aiso; Futoshi Ishiguri; Kazuko Makino; Imam Wahyudi; Yuya Takashima; Tatsuhiro Ohkubo; Kazuya Iizuka; Shinso Yokota (Masyarakat Peneliti Kayu Indonesia, 2017)
The objective of this study was to evaluate the properties for wood utilization of fruit trees planted in Central Kalimantan, Indonesia. A total of 9 jambu bol (Syzygium malaccense), rambutan (Nephelium lappaceum), and durian (Durio zibethinus) trees were randomly selected from the plot (20 by 30 m) and measured for stem diameter, tree height, stress-wave velocity (SWV), and Pilodyn penetration of the trees. Mean values of stem diameter were 11.8, 15.9, and 29.3 cm for S. malaccense, N. lappaceum, and D. zibethinus, respectively. Mean values of stress-wave velocity were 3.16, 3.95, and 3.63 km/s for S. malaccense, N. lappaceum, and D. zibethinus, respectively. Core samples (5 mm in diameter) were collected from these trees to investigate the wood properties [basic density (BD) and compressive strength parallel to grain (CS)], anatomical characteristics [vessel diameter (VD), cell wall thickness (CWT) in wood fiber, and cell length (CL) of wood fiber and vessel element], and amounts of chemical components. In VD, CWT in wood fiber, and CL in wood fiber and vessel element, almost the same radial variation patterns were found in the three species. Relatively higher values in SWV, BD, and CS were found in N. lappaceum, suggesting that its wood can be used for construction lumber. On the other hand, S. malaccense and D. zibethinus had relatively thicker CWT in wood fiber, longer CL in wood fiber, and lower Klason lignin content. It is considered that the wood of these two species may be suitable for pulpwood.